2021
DOI: 10.25115/eea.v39i12.6207
|View full text |Cite
|
Sign up to set email alerts
|

Is Cash Waqf Linked Sukuk (CWLS) Less Than Ideal According to Islamic Laws?

Abstract: As a step to promote public interest in conducting cash waqf, the government launched a program called the National Money Waqf Movement (GNWU) which also introduced Cash Waqf Linked Sukuk (CWLS) Retail Series SWR001 which is a development of the CWLS (SW Series). Both are developments of the Money Waqf and Sukuk (State Sukuk) which have been regulated in the DSN-MUI Fatwa No. 131/DSN-MUI/X/2019. Law No. 41 of 2004, concerning Waqf, and Law No. 19 of 2008, concerning State Sharia Securities (SBSN). CWLS is a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…In addition to the above opinion, another opinion used by the MUI is the opinion of some Hanafi madhhab scholars, namely Abdullah bin Mas'ud who explained that, "what Muslims consider good is good in the sight of Allah, and what Muslims consider bad is bad. in the sight of Allah (Hafandi and Handayati, 2021).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Zakat will also boost the economy through demand and incentives and increase social cohesion. In contrast, waqf has successfully provided public services in the past (Hafandi & Handayati, 2021).…”
Section: The Role and Impact Of Islamic Social Finance In Indonesiamentioning
confidence: 99%